Are point-of-care measurements of glycated haemoglobin accurate in the critically ill?. Issue 6 (November 2019) - Weinel, Luke M.; Summers, Matthew J.; Finnis, Mark E.; Poole, Alexis; Kar, Palash; Chapman, Marianne J.; Deane, Adam M.; Ali Abdelhamid, Yasmine
Abstract: Introduction: Critically ill patients with type 2 diabetes mellitus (T2DM) and chronic hyperglycaemia may benefit from a more liberal approach to glucose control than patients with previously normal glucose tolerance. It may therefore be useful to rapidly determine HbA1c concentrations. Point-of-care (POC) analysers offer rapid results but may be less accurate than laboratory analysis. Aim(s): The aim of this study was to determine agreement between POC and laboratory HbA1c testing in critically ill patients with T2DM. Methods: Critically ill patients with T2DM had concurrent laboratory, capillary-, and arterial-POC HbA1c measurements performed. Data are presented as mean (standard deviation) or median [interquartile range]. Measurement agreement was assessed by Lin's concordance correlation coefficient, Bland–Altman 95% limits of agreement, and classification by Cohen's kappa statistic. Results: HbA1c analysis was performed for 26 patients. The time to obtain a result from POC analysis took a median of 9 [7, 10 ] minutes. Laboratory analysis took a median of 328 [257, 522] minutes from the time of test request to the time of report. Lin's correlation coefficient showed almost perfect agreement (0.99%) for arterial- vs capillary-POC and both POC methods vs arterial laboratory analysis. Bland–Altman plots showed a mean difference of 2.0 (3.7) with 95% limits of agreement of −5.4 to 9.3 for capillary vs laboratory, 1.6 (3.4) and −5.1 to 8.4 for arterial vs laboratory, and −0.137 (2.6) and −5.2 to 4.9 for capillary vs arterial. Patient classification as having inadequately controlled diabetes (>53 mmol/mol) showed 100% agreement across all tests. Conclusions: HbA1c values can be accurately and rapidly obtained using POC testing in the critically ill.